FAST TRACKING IN ADULT CARDIAC SURGERY AT PAKISTAN INSTITUTE OF MEDICAL SCIENCES - Ahmed, Naveed; Khan, Faridullah; Zahoor, Mahrukh; Samad, Badar -ul-; Rafique, Muhammad; Faisal, Muhammad; Sikander, Rana Imran (Journal of Ayub Medical College Abbottabad, 2010)
Background: Early extubation after cardiac operation is an important aspect of fast-track cardiac anaesthesia. The length of stay in ICU limits utilisation of operation theatre in cardiac surgery. Increasing cost, limited resources, and newer surgical strategies have stimulated effectiveness of all routines in cardiac surgery, anaesthesia, and intensive care. Aim of this study was to determine the feasibility of fast-tracking in adult cardiac surgery and its effects on post operative recovery in our setup. Methods: This descriptive study was conducted over 14 months between 16th Jul 2007 to 16th Sep 2008. All the open heart cases were included unless absolute contraindications were there. We applied the rapid recovery protocol adopted from Oslo Hospital Norway in an attempt to achieve fast-tracking in our setup. Results: Two-hundred-seventy-four consecutive cases out of 400 operated cases were included in this study. Mean age was 47.69±15.11 years, 27.7% were females, 5.8% were emergency cases, 5.1% were COPD, 11.1% were atrial fibrillation, and 6.9% were NYHA class-III cases. CABG was done in 66.1% cases and mean CPB-time was 75.92±16.20 min. Mean Ventilation-time was 4.47±4.48 hrs, 86% patients were fast-tracked to be extubated within 6 hours, and 85.4% patients remained free of post-op complications. Six (2.2%) re-intubatIions, 2.6% arrhythmias, 6.6% pleural effusions and 2.2% consolidation were observed post-operatively. Mean ICU stay was 2.49±0.95 days and in-hospital mortality was 2.2%. Conclusion: Fast-tracking with extubation within 6 hours is feasible approach which minimises the post-operative complications significantly in adult cardiac surgical patients. Keywords: Fast-tracking, Adult cardiac surgery, early extubation